2019
DOI: 10.1111/1467-8578.12259
|View full text |Cite
|
Sign up to set email alerts
|

Children’s attitudes towards peers with learning disabilities – the role of perceived parental behaviour, contact experiences and self‐efficacy beliefs

Abstract: Children with special educational needs often feel lonely in classrooms, are less accepted by their classmates and have fewer friendships. Their classmates’ positive attitudes towards them are important for their social participation in inclusive classrooms. According to the theory of social referencing, children’s attitudes towards peers with special educational needs are influenced by the role model behaviour of their parents. Therefore, we examined the relevance of children’s perceptions of parental behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 38 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…For example, high self-esteem reportedly protects children and adolescents from involvement in bullying, both as victims or bullies (O'Moore and Hillery, 1991;Byrne, 1994;Rigby and Cox, 1996;O'Moore and Kirkham, 2001; but also see Olweus, 1993;Slee and Rigby, 1993;Kaukiainen et al, 2002). Importantly, children with better self-beliefs concerning their social competence have more positive attitudes toward peers with disabilities (Hellmich and Loeper, 2019).…”
Section: Self-esteemmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, high self-esteem reportedly protects children and adolescents from involvement in bullying, both as victims or bullies (O'Moore and Hillery, 1991;Byrne, 1994;Rigby and Cox, 1996;O'Moore and Kirkham, 2001; but also see Olweus, 1993;Slee and Rigby, 1993;Kaukiainen et al, 2002). Importantly, children with better self-beliefs concerning their social competence have more positive attitudes toward peers with disabilities (Hellmich and Loeper, 2019).…”
Section: Self-esteemmentioning
confidence: 99%
“…Being the primary agents integrating children into society, parents may significantly influence their children’s attitudes toward out-groups in general and individuals with disabilities in particular ( Hellmich and Loeper, 2019 ). However, previous research showed inconsistent findings relating parents’ and children’s beliefs about people with disabilities: some found positive relation ( Katz and Chamiel, 1989 ; Peck et al, 1992 ; Okagaki et al, 1998 ; Innes and Diamond, 1999 ; Vignes et al, 2009 ; de Boer et al, 2011 , 2012b ; Hellmich and Loeper, 2019 ), while others found no relation ( Aboud and Amato, 2001 ; Perkins and Mebert, 2005 ; Vittrup and Holden, 2011 ; Pahlke et al, 2012 ; Hong et al, 2014 ; Jugert et al, 2016 ).…”
Section: Parental Factors Affecting Perception Of Disabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Children's social participation in early learning centres and/or primary schools depend on their peers' social acceptance. Most often, their personal contact experiences, perception of parental behaviour and self‐efficacy beliefs predict children's attitudes towards their peers 7 . Rodd et al 8 in 2010 stated that children aged 11 to 12 years viewed photographs of children with visible incisor trauma more negatively than the same child with normal incisor appearance, whereas children aged between 14 and 15 years did not.…”
Section: Introductionmentioning
confidence: 99%
“…According to the theory of social referencing, children's attitudes towards peers with special educational needs are influenced by the role model behaviour of their parents. As a result, Hellmich and Loeper (2019) examined the relevance of children's perceptions of parental behaviour in terms of their attitudes towards peers with learning disabilities. This was done by investigating 753 children's attitudes, depending on their perceptions of parental behaviour towards peers with special educational needs, their contact experiences, and their self-efficacy beliefs concerning their interpersonal skills.…”
Section: Literature Reviewmentioning
confidence: 99%